HPB P57 Acalculous Cholecystitis – Does it need a redefinition?. (7th December 2022) - Suresan, Srutti; Shaukat, Mubasher; Ahmad, Reddin; BinSahl, Abdullah; Naeem, Hamza; Peter, Mark
Abstract: Background: Acalculous cholecystitis (AC) is a necroinflammatory disorder of the gallbladder in the absence of gallstones. AC is a diagnostic challenge due to absence of clear published diagnostic criteria. Though diagnosis is dependent upon radiological findings in combination with clinical findings and blood results, it can only be confirmed after analysis of operative findings and post-operative histology. This study aims to assess the correlation between pre-operative imaging and post-operative histology. Methods: Data was retrospectively collected for all patients with a diagnosis of cholecystitis (March 2018 - March 2020) by reviewing ultrasound, computerised tomography and magnetic resonance cholangiopancreatography findings. Patients without any clinical/radiological signs of cholecystitis and with confirmed gallstones on imaging were excluded. A total of 61 patients were identified with AC. Results: Twenty-one patients underwent cholecystectomy at time of data collection. Eleven patients had histological evidence of AC; histology results only showed acute/chronic cholecystitis. Out of these 11 patients, pre-operative imaging from at least one imaging modality showed biliary sludge/microlithiasis in 9 patients. Overall, 13 patients did not have biliary sludge/microlithiasis on pre-operative imaging. Correlating histology results showed 2 patients with gallstones, 1 patient with cholesterolosis, 9 patients with acute/chronic cholecystitis alone and 1 normal gallbladder. Among the 8 patients with biliary sludge/microlithiasis on imaging, histology results identified 1 patient with gallstones, 5 patients with cholesterolosis and 2 patients with acute/chronic cholecystitis alone. Conclusions: Given improvement in diagnostics in detecting biliary sludge, the classical definition of AC may no longer be valid. This study suggests that a new classification may be necessary.